1992
DOI: 10.1084/jem.176.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus transmembrane fusion protein synthesized de novo or presented in immunostimulating complexes is endogenously processed for HLA class I- and class II-restricted cytotoxic T cell recognition.

Abstract: SummaryThe routes used by antigen-presenting cells (APC) to convert the transmembrane fusion glycoprotein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 75 publications
3
56
0
Order By: Relevance
“…We investigated whether binding of MV by LCs results in antigen presentation to MV-specific CD4 1 T cells using the CD4 1 T-cell clone GRIM-F99 that recognizes a peptide derived from the MV envelope glycoprotein F in the context of HLA-DQw1 [30,31]. Activation of the T-cell clone GRIM-F99 does not require full co-stimulation.…”
Section: Captured By Lcs Results In Hla-ii-restricted Antigen Presmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether binding of MV by LCs results in antigen presentation to MV-specific CD4 1 T cells using the CD4 1 T-cell clone GRIM-F99 that recognizes a peptide derived from the MV envelope glycoprotein F in the context of HLA-DQw1 [30,31]. Activation of the T-cell clone GRIM-F99 does not require full co-stimulation.…”
Section: Captured By Lcs Results In Hla-ii-restricted Antigen Presmentioning
confidence: 99%
“…The CD4 1 T-cell clone Hd7 [29], CD4 1 T-cell clone GRIM-F99 [30] and the CD8 1 T-cell clone WH-F40 [31] were cultured as described before.…”
Section: Cellsmentioning
confidence: 99%
“…Activation of CTL responses by ISCOMs was first reported with HIV gp160-ISCOMs and influenza-ISCOMs [102]. Other antigens that have been shown to induce CTL responses in mice after parenteral administration in ISCOMs include OVA [37,96,103], measles virus F-protein [104], RSV [105], mycobacteria hsp60 [106], SIV proteins [107], and HPV E6 and E7 proteins [108]. Intranasal administration of influenza-ISCOMs or ISCOMs containing a CTL epitope of measles virus nucleoprotein linked to a fusion peptide-induced CTL responses [109,110] as did oral immunization with OVA [96,103,111].…”
Section: Activation Of Ctl Responsesmentioning
confidence: 99%
“…Binnendijk et al [104] showed that ISCOMs containing the measles virus F protein sensitized target cells for lysis by CD8 ϩ MHC class I-restricted CTL clones. Sensitization was dependent on cytosolic processing of the F protein to generate peptides presented by MHC class I molecules.…”
Section: Activation Of Ctl Responsesmentioning
confidence: 99%
“…1 TCC recognize MV-infected B-LCL whereas CD4 1 TCC can recognize either MV-infected or antigenpulsed B-LCL [24]. The virus suppression assay as described here has several advantages over the more traditional methods to study cellular immunity: it directly assesses antiviral activity rather than parameters that are associated with the antiviral capacity, like IFN-g production or cytolytic activity.…”
Section: Infectionmentioning
confidence: 99%